Empirical analysis of scaled mixed itinerary-size weibit model for itinerary choice in a schedule-based railway network. Issue 3 (2nd December 2022) - Wen, Keyu; Xie, Jiemin; Chen, Anthony; Wong, S. C.; Zhan, Shuguang; Lo, S. M.; Qiang, Lixia
Abstract : The mixed itinerary-size weibit (MISW) model was recently developed for predicting passengers' itinerary-choice behaviors in a schedule-based railway network. It considers passengers' heterogeneous perceptions and relaxes the independently and identically distributed assumptions of random utility models. However, this model has not been verified using real-world data. Moreover, it is assumed that passengers hold a negative perception of overlapping, but this assumption may not be suitable for all situations. Thus, this study proposes a scaled MISW model which includes a scale parameter to address this issue. We collected passenger ticket-booking data from the South China High-Speed Railway network and conducted an empirical analysis in which we compared the performances of the scaled MISW model and other models (i.e. the multinomial logit, multinomial weibit, and MISW models). According to the results, the scaled MISW model outperformed the other models in describing passengers' choice behaviors in the railway network.